Structural Reforms to Set the Growth Ambition - Rovo, Natasha (World Bank, Washington, DC, 2020)
The effect of structural reforms on growth in Europe and Central Asia is assessed by looking separately at each supply-side channel: capital, labor, and productivity, with the last estimated using the stochastic frontier approach. By controlling for the interaction with the economic cycle, the paper also investigates whether timing matters. Improvements in human capital, regulatory quality, and government effectiveness have the most impact on potential growth, along with financial development. European Union accession may also boost growth, mainly by encouraging capital deepening. However, changes in labor market regulation and tariffs may have ambiguous effects. Applying the results to Serbia, the analysis demonstrates that closing certain structural gaps with the frontier would help boost its potential.